Corporate Governance and Stock Return Volatility - Sari, Dian Mega; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research highlights the importance of corporate governance and helps investors and financial economists understand stock price behaviour after COVID-19. The study aims to find out the influence of the independent board of commissioners, and audit quality on the volatility of share returns in companies operating in the body care product sector and listed in the EIB in 2021-2022. In addition, this study also employs four control variables to avoid the model specification error. The population in this study is a company of body care products listed on the Indonesian Stock Exchange for the year 2021-202. The number of samples used is as many as eight companies in 2021-2022 based on purposive sampling methods that meet the sample selection criteria. The data analytical techniques used are descriptive statistical testing, classical assumption testing, and hypothetical testing using SPSS software version 25 and GRETL. The research results show that the independent board of commissioners and the audit quality influence share return volatility. As a sector directly related to daily consumer needs, the primary consumer goods sector tends to be highly responsive to changing trends and consumer preferences. It makes it interesting research subject to understand how the volatility of share returns in this sector reacts to external and internal factors.